2018
DOI: 10.1186/s13046-018-0786-3
|View full text |Cite
|
Sign up to set email alerts
|

The oncogenic neurotrophin receptor tropomyosin-related kinase variant, TrkAIII

Abstract: Oncogenes derived from the neurotrophin receptor tropomyosin-related kinase TrkA act as drivers in sub-populations of a wide-range of human cancers. This, combined with a recent report that both adult and childhood cancers driven by novel oncogenic TrkA chimeric-fusions exhibit profound, long-lived therapeutic responses to the Trk inhibitor Larotrectinib, highlights the need to improve clinical detection of TrkA oncogene-driven cancers in order to maximise this novel therapeutic potential. Cancers potentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 80 publications
7
57
0
Order By: Relevance
“…14 TrkB belongs to the family of receptor tyrosine kinases (RTKs) and it is believed that some RTKs may act as oncogenes. 33 Our findings showed that TrkB was strongly present in TN, NF, SC, and MPNST, and slightly expressed in GCT. Its high expression confirms what we observed for BDNF and the high affinity of its binding.…”
Section: Discussionsupporting
confidence: 50%
“…14 TrkB belongs to the family of receptor tyrosine kinases (RTKs) and it is believed that some RTKs may act as oncogenes. 33 Our findings showed that TrkB was strongly present in TN, NF, SC, and MPNST, and slightly expressed in GCT. Its high expression confirms what we observed for BDNF and the high affinity of its binding.…”
Section: Discussionsupporting
confidence: 50%
“…Also, Plexin C1 is involved in melanoma progression, its expression is absent in the early stages of the melanoma but occurs in late stages as a pro-survival and anti-apoptotic factor marker and acts via the activation of AKT pathway (81). Interestingly TrkA is considered to be a potential oncogene in malignant melanoma (33), and predominant TrkAIII expression has been detected in metastatic melanoma (39). That may point to the existence of the connection between NTRK1 and PLXCN1 expression in malignant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of the RUNX1-RUNX1T fusion gene, formed as a result of t(8;21) translocation common in pediatric AML, in CD34+ hematopoietic cells induces TrkA expression (37). Recently it was shown that an oncogenic TrkAIII splice isoform was expressed in the thymus and cutaneous melanomas, as well as in the Jurkat T-ALL cell line (38, 39).…”
Section: Introductionmentioning
confidence: 99%
“…The true oncogenic potential of non-fusion NTRK alterations, such as mutations, gene amplifications and alternative splicing has yet to be confirmed [49,50,[82][83][84][85][86]. Moreover, as it will be furtherly discussed later, these alternative types of alterations can play a crucial role in tumor resistance against NTRK-fusions inhibitors and therefore are being increasingly investigated [70,87].…”
Section: The Oncogenic Role Of Ntrk: Fusions Versus Other Alterationsmentioning
confidence: 99%